Efficacy and tolerability of a complex homeopathic drug in children suffering from dry cough-A double-blind, placebo-controlled, clinical trial - Voß, Hans W.; Michalsen, Andreas; Brünjes, Rainer (Drug Research, 2018)
Background A randomised, placebo-controlled clinical trial in children suffering from acute dry cough was performed to assess the efficacy and tolerability of a complex homeopathic drug (Drosera, Coccus cacti, Cuprum Sulfuricum, Ipecacuanha=Monapax syrup, short: verum).Methods 89 children received verum and 91 received placebo daily for 7 days (age groups 0.5–3, 4–7 and 8–12 years). The primary efficacy variable was the improvement of the Cough Assessment Score. Tolerability and compliance were also assessed. A confirmatory statistical analysis was performed for the primary efficacy variable and a descriptive analysis for the secondary parameters.Results The Cough Assessment Score showed an improvement of 5.2±2.6 points for children treated with verum and 3.2±2.6 points in the placebo group (p<0.0001). The difference of the least square means of the improvements was 1.9±0.4. The effect size of Cohen´s d was d=0.77. In all secondary parameters the patients in the verum group showed higher rates of improvement and remission than those in the placebo group. In 15 patients (verum: n=6; placebo: n=9) 18 adverse drug reactions of mild or moderate intensity were observed.Conclusions Administering verum resulted in a statistically significantly greater improvement of the Cough Assessment Score than the placebo. The tolerability was good and not inferior to that of the placebo.
Keywords: Homeopathy; paediatric; clinical trial; placebo; cough assessment score